Phylogenetic lineages in the Botryosphaeriaceae - Crous, Pedro W. (CBS Fungal Biodiversity Centre, 2006)
Botryosphaeria is a species-rich genus with a cosmopolitan distribution, commonly associated with dieback and cankers of woody plants. As many as 18 anamorph genera have been associated with Botryosphaeria, most of which have been reduced to synonymy under Diplodia (conidia mostly ovoid, pigmented, thick-walled), or Fusicoccum (conidia mostly fusoid, hyaline, thin-walled). However, there are numerous conidial anamorphs having morphological characteristics intermediate between Diplodia and Fusicoccum, and there are several records of species outside the Botryosphaeriaceae that have anamorphs apparently typical of Botryosphaeria s.str. Recent studies have also linked Botryosphaeria to species with pigmented, septate ascospores, and Dothiorella anamorphs, or Fusicoccum anamorphs with Dichomera synanamorphs. The aim of this study was to employ DNA sequence data of the 28S rDNA to resolve apparent lineages within the Botryosphaeriaceae. From these data, 12 clades are recognised. Two of these lineages clustered outside the Botryosphaeriaceae, namely Diplodia-like anamorphs occurring on maize, which are best accommodated in Stenocarpella (Diaporthales), as well as an unresolved clade including species of Camarosporium/Microdiplodia. We recognise 10 lineages within the Botryosphaeriaceae, including an unresolved clade (Diplodia/Lasiodiplodia/Tiarosporella), Botryosphaeria s.str. (Fusicoccum anamorphs), Macrophomina, Neoscytalidium gen. nov., Dothidotthia (Dothiorella anamorphs), Neofusicoccum gen. nov. (Botryosphaeria-like teleomorphs, Dichomera-like synanamorphs), Pseudofusicoccum gen. nov., Saccharata (Fusicoccum- and Diplodia-like synanamorphs), “Botryosphaeria” quercuum (Diplodia-like anamorph), and Guignardia (Phyllosticta anamorphs). Separate teleomorph and anamorph names are not provided for newly introduced genera, even where both morphs are known. The taxonomy of some clades and isolates (e.g. B. mamane) remains unresolved due to the absence of ex-type cultures.